Pregnancy in acromegaly is safe and is associated with improvements in IGF-1 concentrations. Issue 4 (April 2019) - Hannon, Anne Marie; O'Shea, Triona; Thompson, Claire A; Hannon, Mark J; Dineen, Rosemary; Khattak, Aftab; Gibney, James; O'Halloran, Domhnall J; Hunter, Steven; Thompson, Christopher J; Sherlock, Mark
Abstract : Pregnancy is rarely reported in acromegaly. Many patients are diagnosed in later life and younger patients may have subfertility due to hypopituitarism. We present a case series of 17 pregnancies in 12 women with acromegaly. Twelve women with acromegaly who completed pregnancy were identified from centres involved in the Irish Pituitary Study. Eleven women had pituitary macroadenomas and one woman had a microadenoma. Only 5/17 pregnancies had optimal biochemical control of acromegaly preconception, as defined by IGF-1 concentration in the age-related reference level and plasma GH concentration of <2 μg/L. In 6/17 pregnancies, dopamine agonist treatment was continued during pregnancy; all other acromegaly treatments were discontinued during pregnancy. Effect of pregnancy on acromegaly : No patient developed new visual field abnormalities, or symptoms suggestive of tumour expansion during pregnancy. In 9/12 patients, plasma IGF-1 concentrations that were elevated preconception normalised during pregnancy. There was a reduction in plasma IGF-1 concentrations, though not into the normal range, in a further two pregnancies. Effect of acromegaly on pregnancy : 15 healthy babies were born at term; one patient underwent emergency C-section at 32 weeks for pre-eclampsia, and one twin pregnancy had an elective C-section at 35 weeks' gestation. Blood pressure remained within normal limits in the remainder of the pregnancies. Gestational diabetes did not develop in any pregnancy. Our data suggests that pregnancy in women with acromegaly is generally safe, from a maternal and foetal perspective. Furthermore, biochemical control tends to improve despite the withdrawal of somatostatin analogue therapy during pregnancy.